Distribution of Angiotensin-1 Converting Enzyme Insertion/Deletion and alpha-Actinin-3 Codon 577 Polymorphisms in Turkish Male Soccer Players - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2015)
Angiotensin-1 converting enzyme (ACE) gene and a-actinin-3 (ACTN3) gene polymorphisms are considered to be the most important candidate genes for genetic predisposition to human athletic performance. In the present study, we aimed to analyze the distribution of ACE and ACTN3 polymorphisms for the first time in male Turkish soccer players. In this prospective study, our cohort consisted of 25 professional players, all with Turkish ancestry. Polymerase chain reaction (PCR)-restriction length polymorphism was used for the characterization of the genotype of ACTN3 and single PCR for ACE. For ACE genotype, 16%, 44%, and 40% of the players had insertion/insertion (II), insertion/deletion (ID), and deletion/deletion (DD) genotypes, respectively, whereas 20% had XX, 36% had RX, and 44% had RR genotypes for ACTN3. When we examined the allelic percentages, for ACE, D allele was recorded as 62 and I as 38, and for ACTN3, R allele was 62 and X was 38. Our results were in agreement with the previous reports, indicating the presence of ACTN3 D and ACE X allele in soccer players. We suggest that ACE and ACTN3 genotypes are important biomarkers for genetic counseling for the individuals who are prone to be successful soccer players.
Keywords: ACE; ACTN3; soccer; polymorphism; sport genetics